South Africa’s foreign policy aspirations and the National Development Plan (ndp 2030): the role and impact of trade and investment on the state’s political economy - Chabalala, Katekani (My University, 2021)
In August 2012, South Africa launched the National Development Plan (NDP) to address the poverty, unemployment and inequality challenges prevalent in the domestic political economy. President Cyril Ramaphosa was confronted with a problem upon assuming office in 2018 – how to address the slow progress in the implementation of the NDP. This study contends that while the NDP has guided South African government departments’, some of the core ideas on foreign policy have not been implemented. The case study analysis explores South Africa’s trade and investment relations with Nigeria, China and the United States. The empirical findings reveal that the constraints in the implementation of South Africa’s economic diplomacy are the slow progress in Africa’s regional integration, and the lack of capabilities to manufacture technology-intensive products. It explains several trends that have emerged and present implications for the future direction of South Africa’s economic diplomacy, this includes the proliferation of free trade agreements, and policy uncertainty on how to advance transformation.
A research report submitted in partial fulfilment of the requirements for the Master of Arts in International Relations by coursework and research report to the Faculty of Humanities, Wits School of Social Sciences, University of the Witwatersrand, 2021